The role of "digitalization" in German sustainability bank reporting - Florian Diener; Miroslav Špaček (International Journal of Financial Studies, 2020)
The financial services sector, particularly with respect to today's banking industry, is aiming to make a digital transition. Sustainable reporting is a holistic new reporting approach in banking and has only become partially mandatory for the sector. Thus, this paper makes a contribution to the current analysis approach and further development of the German Sustainability Code as well as associated legal approaches. It concerns the assessment of mandatory sustainable reporting in the light of constantly changing market conditions and stricter legal requirements for stakeholder data responsibility. In specific, it focuses on a digital evolving business environment and is intended to provide an insight into the perception of the topic of digitalization in the banking sector. The assessment is based on the structure of the German Sustainability Code. Based on 113 bank reports, a multiple regression analysis of 1410 codings of the keyword "digital" is carried out. The results show that banks partly and not fully address digital issues in their reporting. It transpires that the emphasis is on seven criteria, while social elements are totally ignored. The paper shows a structural inequality within sustainable bank reporting with regard to digitalization. It also shows that issues are not adequately addressed and covered in legal reporting standards and that the provision of information to stakeholders on specific issues is largely undefined.
Keywords: G20; G21; O30; O33; Q56; 330; bank; digital; digitalization; financial services; innovation; reporting; strategy; sustainability